Behavioral Constraints on the Design of Subgame-Perfect Implementation Mechanisms - Ernst Fehr; Michael Powell; Tom Wilkening (American Economic Review, 2021)
We study subgame-perfect implementation (SPI) mechanisms that have been proposed as a solution to incomplete contracting problems. We show that these mechanisms, which are based on off-equilibrium arbitration clauses that impose large fines for lying and the inappropriate use of arbitration, have severe behavioral constraints because the fines induce retaliation against legitimate uses of arbitration. Incorporating reciprocity preferences into the theory explains the observed behavioral patterns and helps us develop a new mechanism that is more robust and achieves high rates of truth-telling and efficiency. Our results highlight the importance of tailoring implementation mechanisms to the underlying behavioral environment. (JEL C92, D44, D82, D86, D91)
Keywords: C92; D44; D82; D86; D91; 330